2012
DOI: 10.1523/jneurosci.2107-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Cleavage Product GLP-1(9-36) Amide Rescues Synaptic Plasticity and Memory Deficits in Alzheimer's Disease Model Mice

Abstract: Glucagon-like peptide-1 (GLP-1) is an endogenous intestinal peptide that enhances glucose-stimulated insulin secretion. Its natural cleavage product GLP-1 (9-36)amide possesses distinct properties and does not affect insulin secretion. Here we report that pretreatment of hippocampal slices with GLP-1(9-36)amide prevented impaired long-term potentiation (LTP) and enhanced long-term depression (LTD) induced by exogenous amyloid β peptide (Aβ1-42). Similarly, hippocampal LTP impairments in APP/PS1 mutant mice tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 45 publications
5
78
0
Order By: Relevance
“…In the pancreatic islets, the GLP-1 receptor is internalized after GLP-1-induced activation (20)(21)(22)(23) and passes through recycling endosomes before it appears in the plasma membrane again (23). The GLP-1 receptor is widely distributed in the brain (10, 16,24), including in the hippocampal CA3 pyramidal neurons (16,25), and GLP-1 and other agonists at the GLP-1 receptor have been reported to regulate food intake (26), be neuroprotective (27), anti-inflammatory (28), and modulate synaptic plasticity and memory formation (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…In the pancreatic islets, the GLP-1 receptor is internalized after GLP-1-induced activation (20)(21)(22)(23) and passes through recycling endosomes before it appears in the plasma membrane again (23). The GLP-1 receptor is widely distributed in the brain (10, 16,24), including in the hippocampal CA3 pyramidal neurons (16,25), and GLP-1 and other agonists at the GLP-1 receptor have been reported to regulate food intake (26), be neuroprotective (27), anti-inflammatory (28), and modulate synaptic plasticity and memory formation (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Neuronal cell line studies and AD rodent models showed that GLP‐1 and GIP ameliorated oxidative stress‐induced injury76, 80, 85, 86, and protected against cell death induced by Aβ42, 88. Furthermore, various studies reported that D‐Ala 2 GIP reduced the inflammatory response in rodent AD models81, 83, 85.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
“…In rodent models of AD, peripherally‐administered geniposide and D‐Ala 2 GIP reduced levels of Aβ plaque load81, 83, 84, 85. However, two other studies reported no reduction of both APP and Aβ levels, despite the fact that treatment did have beneficial effects on memory or LTP82, 86. Peripherally‐administered liraglutide reduced both Aβ and APP levels72, even in a late‐stage AD rodent model75.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
“…When GLP-1 binds to GLP-1r it stimulates B cell proliferation, it inhibits apoptosis, favors glucose mediated insulin secretion, achieving glucose homeostasis, lowering food intake. Other functions of GLP-1 include the reduction in glucagon secretion, the inhibition of gastrointestinal motility, the inhibition of hepatic glucose production and release, inhibition of overall gluconeogenesis and glucogenolysis, acting at hypothalamic level to reduce appetite and increasing sensitivity to insulin, among others [10].…”
Section: Glp-1mentioning
confidence: 99%